Neutrophil expansion defines an immunoinhibitory peripheral and intratumoral inflammatory milieu in resected non-small cell lung cancer: a descriptive analysis of a prospectively immunoprofiled cohort. Issue 1 (28th April 2020) - Mitchell, Kyle G; Diao, Lixia; Karpinets, Tatiana; Negrao, Marcelo V; Tran, Hai T; Parra, Edwin R; Corsini, Erin M; Reuben, Alexandre; Federico, Lorenzo; Bernatchez, Chantale; Dejima, Hitoshi; Francisco-Cruz, Alejandro; et al.
Abstract : Background: The biological underpinnings of the prognostic and predictive significance of a relative neutrophilia in patients with non-small lung cancer (NSCLC) are undefined. We sought to comprehensively examine the relationships between circulating and intratumoral neutrophil populations and features of the immune contexture in patients undergoing NSCLC resection. Methods: Preoperative soluble cytokine and angiogenic factors; tumor multiplex immunofluorescence; RNA, whole exome, and T-cell receptor sequencing; and flow cytometry were analyzed for relationships with populations of circulating (from complete blood counts) and intratumoral neutrophils (transcriptional signatures) in a prospectively enrolled resected NSCLC cohort (n=66). In a historical cohort (n=1524), preoperative circulating neutrophil and lymphocyte counts were analyzed for associations with overall survival (OS). Results: Circulating neutrophil populations were positively correlated with increased tumor burden, and surgical tumor resection was followed by a subsequent reduction in peripheral neutrophil counts. Expansion of the circulating neutrophil compartment was associated with increased levels of pro-granulopoietic (IL-1β, IL-17A, TNFα, IL-6) and TH 2-associated (IL-5, IL-13) cytokines. Tumors with high intratumoral neutrophil burden were marked by a blunted T-cell response characterized by reduced expression of cytotoxic T-cell genes ( CD8A, CD8B, GZMA, GZMB ), decreased CD3 + CD8 + cell infiltration, and diminished expression of IFNγ-related genes. The associations between increased intratumoral neutrophil burden and reduced CD3 + CD8 + infiltration persisted after adjustment for tumor size, histology, mutational burden, and PD-L1 expression. In 1524 patients, elevated preoperative circulating neutrophil count was independently associated with worse OS (main effect HR 1.82, 95% CI 1.24 to 2.68, p=0.002). Conclusions: Our findings demonstrate that neutrophil expansion reflects protumorigenic and immunosuppressive processes that manifest as worse OS in patients undergoing NSCLC resection. These results justify further investigation of therapeutic strategies targeting neutrophil-associated immune evasion.